Role of src splice variants in nerve terminal function - Abdelhameed, Taher (The University of Edinburgh, 2010)
Src is a 60 kDa tyrosine kinase that is expressed in most of animal tissues. Src has three splice variants, C-src, which is ubiquitously expressed, and N1- and N2-src, which are neuronal specific splice variants. The srcs are differentially spliced at their SH3 domains, therefore the hypothesis is that this splicing allows them to have different binding partners and perform different roles in neurons. The aim of this project is to identify new interactions for the three src splice variants in neurons and their possible functional roles. The SH3 domains, kinase active truncated proteins ( 80) and kinase dead mutant full length versions of the three splice variants of src were cloned from a rat brain cDNA library into bacterial expression vectors. GST-pull downs from nerve terminal lysates showed that different src splice variants had different binding partners. These partners were identified by mass spectrometry and confirmed by western blotting. C-src binding partners included dynamin, synapsin, and synaptojanin, while N2-src binding partners included synaptophysin, Munc18-1, and NSF. The interaction between N2-src and Munc 18-1 was characterized further; however a number of in vitro interaction assays and kinase assays showed that Munc 18-1 may not be a direct binding partner for N2-src or substrate. N1-src displayed a stimulation-dependent interaction with dynamin I. This was shown to be phosphorylation-dependent in contrast to C-src binding. The major phosphorylation sites on dynamin I, S774 and S778, were not involved in the regulation of N1-src binding. The binding site for N1-src on dynamin I was different to C-src, with extensive mutagenesis studies suggesting that the interaction site is at the tail of the dynamin I xa splice variant, which has an additional two phosphorylation sites.
Keywords: src; nerve terminal; endocytosis; exocytosis